Thin film flow on a vertically rotating disc of finite thickness partially immersed in a highly viscous liquid. (2nd April 2016) - Miah, Md Salim; Al-Assaf, Saphwan; Yang, Xiaogang; McMillan, Alison
Abstract: The entrainment and flow of a thin film of liquid on a vertically rotating disc partially immersed in a liquid bath has been investigated experimentally and modelled numerically. The Volume of Fluid (VOF) Computational Fluid Dynamics (CFD) modelling approach has been employed to characterise the shape and stability of the thin film thickness profile. The thickness of the rotating disc plays a significant role in the thin film profile and this is confirmed through the comparison of simulation with the experimental results. Other factors determining the film thickness were identified as the rotational speed and the fluid viscosity where the film thickness profile increases with the increase of the rotational speed and also the viscosity. A correlation equation to predict the film thickness as a function of angular position, radius, rotating speed, viscosity and surface tension is proposed. The results given in this study specifically report on the thin film thickness variation with the angular direction and the film entrained into the liquid. In both the simulation and experimental results, it is noted that the film thickness stabilises following a rotation of 15° after drag out of the liquid, and remains so until 10° before being dragged back in. Highlights: The film formation is investigated experimentally and modelled numerically. A correlation equation has been proposed to predict the film thickness. The experimental measurements were conducted using the laser scan method. Numerical modelling was performed using the Volume of Fluid method. The rim thickness of the disc was found to have a measurable effect on the film profile.